Association of brain copper with Alzheimer's disease neuropathology: A community‐based neuropathologic study: Human neuropathology/clinicopathologic correlations. (7th December 2020) - Agarwal, Puja; Dhana, Klodian; Schneider, Julie A.; Ayton, Scott; Wang, Yamin; Agrawal, Sonal; Bennett, David A.; Barnes, Lisa L.; Leurgans, Sue E.; Bush, Ashley I.; Morris, Martha Clare
Abstract: Background: Copper (Cu) is an essential element for brain health. There is increasing recognition that altered Cu homeostasis is related to the development of Alzheimer's disease (AD). Neuropathologic findings of amyloid plaque and neurofibrillary tangles are the hallmarks of Alzheimer's disease process. Whether brain Cu is associated with AD neuropathology in humans is unknown. This study examines the relationship between brain Cu levels and AD neuropathology in autopsies from a community sample of older adults. Method: The study was conducted in 679 deceased participants from the Rush Memory and Aging Project, a cohort study. Brain Cu levels were measured using ICP‐MS in gray matter from inferior temporal, mid frontal, anterior cingulate, and cerebellum. Diffuse and neuritic plaques and neurofibrillary tangles were assessed in multiple brain regions and summarized as standard measures of AD pathology, including Braak, CERAD, NIA‐Reagan, global AD pathology. Linear regression analyses were used to evaluate the associations of brain Cu (grouped in tertiles) with the AD pathology in models controlled for age at death, sex, education, and APOE‐ ε 4 status. Result: The mean age at death was 90.2 (±6.2) years, 70% were women, and 25% carriers of the APOE4 allele. Higher brain Cu levels were associated with less AD neuropathology. Participants in the middle and highest tertile of overall brain Cu levels had less global AD pathology (T3 vs. T1:β = ‐0.10; T2 vs. T1 = ‐0.11; p trend = 0.007) and Braak stage (T3 vs. T1: β = ‐0.31; T2 vs. T1 = ‐0.22; p trend = 0.005) when compared to those in the lowest tertile. Similar associations were found between inferior temporal brain Cu levels and AD neuropathology: global AD pathology (T3 vs. T1: β = ‐0.17, p = <0.0001); Braak (T3 vs. T1: β = ‐0.42, p = 0.0001); CERAD (T3 vs. T1: β = ‐0.17, p = 0.008); NIA‐Reagan (T3 vs. T1: β = ‐0.21, p = 0.002)). Brain Cu levels in mid‐frontal and cerebellum had a marginal association, whereas anterior cingulate Cu levels had no association with AD neuropathology. Conclusion: Higher brain copper levels are associated with fewer AD neuropathology, suggesting that brain Cu levels either may reflect the severity of the disease or may indicate its potential beneficial effect on the disease process.